Concept of Madataya (Alcoholism): “An Ayurvedic Review” - Mahapatra, Trupti; Inchulkar, S R (International Research Journal of Ayurveda & Yoga, 2022)
Agad tantra is the branch of Ayurveda which deals with poison and its management. There is no such difference between poison and addiction. Poison and addiction both are hazardous for health. The substance causing Mada produces disturbances of intellect faculty by its virtue of tamo gunas called madya. The properties of madya is all most equal to visha. Improper, excess intake of madya can be hazardous to health and may result in death while proper dosage gives health and pleasure. Action of drug depends upon various factors like its matra (dose), avacharana (mode of administration) etc.so, it is important to know the properties of substance that will decide how it going to affects the body. so, here is an effort made to see the detail of ayurvedic concepts of Madya.